2011
DOI: 10.5586/asbp.2007.006
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in plant cells, its physiological role and changes under heavy metal stress

Abstract: Lipid peroxidation, which is a natural and essential process, can occur in a non-enzymatic and/or enzymatic way in plant cells. Some of its products have cytotoxic effects on cells, but others function as plant effectors. The lipid peroxidation in plants exposed to heavy metal stress depends on the metal, plant organ, plant species and its genotype.KEY WORDS: heavy metal stress, lipid peroxidation, lipoxygenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 51 publications
0
30
0
3
Order By: Relevance
“…However, differences have been noted in the changes in chlorophyll levels in response to UV between different genotypes and we observed that Ke83 and Pinot Blanc did not show an increase in chlorophyll levels to the extent shown by Hoe29 and Ke53. Citrus sinensis and Arabidopsis thaliana did not show chlorophyll degradation after a short UV exposure, indicative of some stress‐resistance and adaptability (Harpaz‐Saad et al , Sakuraba et al 2014). The Augster Weiss and Müller–Thurgau genotypes did not synthesize high levels of stilbenes over the UV‐C stress time course (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, differences have been noted in the changes in chlorophyll levels in response to UV between different genotypes and we observed that Ke83 and Pinot Blanc did not show an increase in chlorophyll levels to the extent shown by Hoe29 and Ke53. Citrus sinensis and Arabidopsis thaliana did not show chlorophyll degradation after a short UV exposure, indicative of some stress‐resistance and adaptability (Harpaz‐Saad et al , Sakuraba et al 2014). The Augster Weiss and Müller–Thurgau genotypes did not synthesize high levels of stilbenes over the UV‐C stress time course (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3), especially in the case of Augster Weiss. This may indicate a less effective response mechanism: the UV‐C radiation might cause the destruction of photosynthetic membranes and ultrastructure of the chloroplasts (Brandle et al 1977), or it might impair the activity of photosystem II (PSII) and related proteins (Fagerberg , van Rensen et al , Gupta et al 2008, Dobrikova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu zararlı etkilerden en belirgini hücre zarı lipitlerinin peroksidasyonu yoluyla hücreye verilen hasardır. Bu noktada, oluşan malondialdehit (MDA) miktarının ölçülmesi bitkideki hücresel hasarın düzeyi ile ilgili bir belirteç olabilir (Skórzyńska-Polit 2007).…”
Section: Introductionunclassified
“…Studies on how plant genotypes respond to all kind of stresses indicate a similar mechanism of adaptation to unfavorable environmental conditions. These reactions are mostly connected with neutralizing free radicals, particularly reactive oxygen species (ROS) which frequently appear as the effect of different stress factors [1][2][3]. Many experiments indicate significance changes in the enzymatic and non-enzymatic antioxidant system during environmental stresses in plant tissues.…”
Section: Introductionmentioning
confidence: 99%